1983
DOI: 10.1016/0014-5793(83)80899-0
|View full text |Cite
|
Sign up to set email alerts
|

(5‐demethyl)‐Bacteriorhodopsin analogue: its formation and light‐driven proton pump action

Abstract: The binding of the isomers fall-trans, tfcis, f f-c& and 94s) of ~~~~~t~~lr~t~~~ to ~~~t~~i~o~~~~ and the light-dark adaptation as well as the tight-driven proton pump action of the resulting bacteriorhodopsin analogue were studied. The (Sdemethyl)-bacteriorhodopsin is formed -3-times faster than unmodified bacteriorhodopsin and shows an efficient light-driven proton pump action. These findings show that upon binding of retinal to bacterioopsin the protein forces the chromophore to adopt a more planar ring-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We found that the presence of a methyl group at position C 5 or the methyls at C 1 is crucial for the ring orientation and locking the retinal chromophore in a conformation that allows formation of the chromophore–protein covalent bond. In analogy to bR, the methyl at position 1 or 5 is probably required for specific retinal–protein interactions that induce a ring–chain retinal planar conformation within its binding site. , The phenylretinal that does not bear any bulky groups and has a planar conformation is able to form a covalent bond with Lys-240, even though it lacks the crucial methyl group at position C 5 . It is evident that its ability to form a stable pigment does not correlate with its relatively small size in the ring area, as the linear analogue that lacks the ring did not form a pigment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the presence of a methyl group at position C 5 or the methyls at C 1 is crucial for the ring orientation and locking the retinal chromophore in a conformation that allows formation of the chromophore–protein covalent bond. In analogy to bR, the methyl at position 1 or 5 is probably required for specific retinal–protein interactions that induce a ring–chain retinal planar conformation within its binding site. , The phenylretinal that does not bear any bulky groups and has a planar conformation is able to form a covalent bond with Lys-240, even though it lacks the crucial methyl group at position C 5 . It is evident that its ability to form a stable pigment does not correlate with its relatively small size in the ring area, as the linear analogue that lacks the ring did not form a pigment.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the 5-methyl (12, R = H) produces a pigment which is reported to reduce the proton-pumping efficiency by 40%. 18 The 5-ethyl (12, R = Et) and 5-methoxy (12, R = OMe) retinals form stable pigments which exhibit some proton-pumping activity.'? 5-Bromo-bR (containing 12, R =Br, as chromophore) has only 11% of the proton-pumping activity of bR,20 whereas the blue-shifted 5-trifluoromethyl-bR (12, R =CF 3 , "' max 465 nm) is nonfunctional."…”
Section: Ia-ii Side-chain Substituentsmentioning
confidence: 99%